PEMANFAATAN TEKNOLOGI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS UNTUK ANALISIS SPASIAL TINGKAT KEKERINGAN WILAYAH KABUPATEN TUBAN - Sukojo, Bangun Muljo; Prayoga , Muhharama Putra (GEOID, 2017)
Tuban Regency is one of the districts in East Java which is a drought-prone area. Based on the Indonesian Disaster Risk Index (IRBI) data released by the Disaster Management Agency (BNPB) in 2013, Tuban received a score of 24 for the drought disaster risk index, which scores are categorized as high risk for drought. The purpose of this research is to know the distribution of drought risk areas in Tuban Regency by utilizing remote sensing data integrated with the physiographic condition of the region that affect the drought which is then grouped into 5 classes of drought levels, namely: very low, low, medium, high, and very high . The data required in this study are: Normalized Different Vegetation Index (NDVI) map, Normalized Different Water Index (NDWI) map, Land Surface Temperature (LST) map, average rainfall map, hydrogeological map, and land use map. From the data processing, it is found that most of the area in Tuban Regency is categorized into a high drought category of 119,388.50 hectares or 60.60% of the total area, while the lowest is the very low drought category that is only 180.48 hectares or 0.09 % of total area. Keywords: Tuban Regency, Drought, Remote Sensing, Geographic Information System.